English vocabulary enrichment in the view of sociocultural contact and development - Subekhi Hadi Purnomo (Jurnal Linguistik Terapan, 2011)
The cultural and language contacts have occurred in the English language for centuries, and enriched its vocabulary. This article reviews how English vocabulary was enriched from the view of sociocultural contact and development. European Countries' Colonization of England has surely shown some influence on English vocabulary. This can be traced from words that can be referred back to the influence of Roman and Saxon cultures (German, Norman, and French cultures). Interestingly, English was also enriched by the languages of the countries England colonized (e.g. Czech, Dakota, Danish, Dutch, Egyptian, Finnish, German, Guarani, Gullah, and Haitian). In the modern era, English vocabulary is influenced by politics, economy, social affairs and religions. This proves that language is an important part of culture, and culture contact always leads to language contact.